An Overview and Critique of NCAA Policy Regarding the Use of Sport Psychology Consultants at the Division I Level - Bemiller, James H.; Wrisberg, Craig A. (Journal of Intercollegiate Sport, 2011)
Over the past 20 years the National Collegiate Athletic Association Division-I (NCAA) has restricted the activities of sport psychology consultants (SPCs) working with student-athletes, particularly at the Division I (D-I) level. In some cases, the restrictions have been based on the assumption that what SPCs do is actually “coaching.” Thus, if SPCs are permitted to interact with student-athletes during practices and competitions they must be considered as “countable” coaches. In this paper, we briefly discuss the history of NCAA rules governing the activities of SPCs, provide excerpts from the sport psychology literature and the NCAA D-I Manual that illustrate how the specialized work of SPCs is different from that of coaches, suggest reasons why allowing student-athletes and coaches access to SPCs during practices and competitions would be beneficial to both groups, and propose ways NCAA legislation might be amended to allow SPCs to work with student-athletes in a manner similar to the ways other athletic department support personnel (e.g., athletic trainers and strength and conditioning coaches) are permitted to do.